Komposisi dan Struktur Seedling dan Sapling pada Lahan Pra dan Pasca Tambang Batubara PT. SLN di Kabupaten Dharmasraya - - Solviana; Erizal Mukhtar; - Chairul (Jurnal Biologi Universitas Andalas, 2012)
Research about composition and structure seedling and sapling at pre and post coal mining PT. SLN have been carried out from April to July 2012 by using the belt transect with quadrate plot of size 10 x 10 m2. The results showed the composition of seedling at pre-mining was 6 families, 6 genera, 6 species and 38 individuals. In case of the composition of post coal mining was 4 families, 3 genera, 5 species and 20 individuals. Furthermore, the composition of sapling at pre coal mining was 12 families, 35 genera, 43 species and 304 individuals. In case of the composition of post coal mining was 6 families, 8 genera, 10 species and 102 individuals. The highest importance value for seedling at pre mining was Canthium dicoccum (47.37 %) and at post mining was Clibadium surinamense (58.18 %). The highest importance value for sapling at pre mining was Hevea brasiliensis (20.27 %) and at post mining was Macaranga tanarius (46.11 %). Diversity index of seedling at pre mining was 1.69 % and in post-mining was 1.55 %, where as for the sapling at pre mining was 3.51 % and at post mining was 2.16%. Index similarity seedling and sapling were 18 % and 3.8 % respectively.Keyword:composition, structure, pre and post coal mining, seedling, sapling